Analysis of Pyogenic Liver Abscesses in a Tertiary Care Hospital - Muhammad Ayyaz, Bushra Gohar Shah, Anil Iqbal, Tariq Tahir Butt, Ayesha Shafique (Pakistan Journal of Medical & Health Sciences, 2022)
PLA (Pyogenic Liver Abscess) is a fatal disease. It is quite difficult to diagnose this disease at the early stages. Huge changes were observed in the epidemiology and mortality of this disease in past years. For a more efficient diagnosis of this illness, there is a need to understand the pathological cycle of this disease. Objective: Due to the lack of diagnostic methods for early detection of PLA (Pyogenic Liver Abscess), it is impossible to treat and control this illness; there is a need to understand the pathogenicity of the disease to find the most appropriate way of detection. To find a suitable detection method is necessary for the further treatment and eradication of the disease. Study Design: It is a retrospective study with statistical approach, conducted in Medicine of Department of M. Islam Medical and Dental College Gujranwala for six months duration from July 2021 to December 2021. Methods: To find an appropriate diagnostic method for the detection of Pyogenic liver abscess, samples of 118 patients were selected. The clinical data related to pathogenicity, symptoms of illness, demographic distribution, treatment history, and the mortality rate was carefully noted, Patients were non-amoebic illnesses were selected for this study. Leukocytes and C-reactive protein values of the patients were also estimated. Microbes involved in this disease were also identified Results: The microbe involved in PLA was Klebsiella pneumonia. This disease was more prevalent in males in the age group 57 years. In more severe patients WBCs level was significantly high and CRP values were also aroused much. 67 % of patients have a high level of leukocytes. The mortality rate was about 6 % in these patients. Conclusion: After complete demographic, clinical, C-reactive protein level, evaluation of leukocytes, imaging results by ultrasound might help to diagnose this disease at an early stage. For the treatment of illness, image guided catheter and proper usage of antibiotics is recommended.